Implementation of Portable Digital Chest X-ray Machine for Tuberculosis Contact Tracing in Oyo and Osun States, Nigeria: A Formative Assessment - Patrick Dakum; Aderonke Agbaje; Olugbenga Daniel; Chukwuma Anyaike; Obioma Chijoke-Akaniro; Evaezi Okpokoro; Samuel Akingbesote; Christian Anyomi; Adekola Adekunle; Abiola Alege; Moroof Gbadamosi; Olutunde Babalola; et al. (MDPI AG, 2024)
This paper presents a formative assessment for the implementation of mobile portable chest X-ray (PDX) machines for tuberculosis (TB) contact tracing in the Oyo and Osun states, Nigeria. This descriptive qualitative study was carried out in eight local government areas, and 24 focus group discussions and 30 key informant interviews were conducted using a four-stage sampling technique to select participants. Validated transcribed notes were entered and analyzed using Nvivo. The respondents' ages ranged from 17 to 85 years, with a mean age of 42.08 ± 14.9 years, and 4.0% had a postgraduate degree. The majority of government officials stated that deploying the PDX machine for screening at the community level is the best means for implementation because it will offer a level of proximity convenience to the TB contacts and assuage concerns about the cost of transportation to the health facility. In addition, it was suggested that TB community screening should be carried out with screening for other health conditions such as high blood pressure and diabetes. This portable X-ray machine intervention, therefore, should be implemented at the community level for contact tracing to allow more TB contacts living with the index patient to be screened without proximity and transportation constraints.